ANALYSIS OF DOMESTIC AND INTERNATIONAL TOURIST ACCEPTANCE OF ANIMAL WELFARE CERTIFIED ANIMAL PRODUCTS - Dian Kristi; Kadek Karang Agustina; I Wayan Sukernayasa (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
The implementation of animal welfare is an important aspect of sustainable livestock systems as it directly affects the quality and safety of animal products. Increasing global awareness of ethical issues has driven demand for animal welfare–certified products, particularly in tourist destinations such as Bali. This study aims to analyze the level of knowledge, attitudes, and acceptance of domestic and international tourists toward animal welfare–certified animal products in Bali. The study employed an observational method with a descriptive quantitative and qualitative approach, involving 222 respondents consisting of 111 domestic tourists and 111 international tourists. Data were collected through questionnaires and analyzed descriptively, as well as using the Mann–Whitney test to identify differences between groups. The results showed that international tourists have a higher level of knowledge compared to domestic tourists, particularly regarding the concepts, indicators, and certification of animal welfare. Both groups demonstrated positive attitudes; however, international tourists exhibited a higher level of acceptance, reflected in their purchase intention, willingness to pay more, and tendency to choose and recommend certified products. There were highly significant differences between the two groups in terms of knowledge as well as attitudes and acceptance (p < 0.01). It can be concluded that the level of knowledge plays an important role in shaping consumer attitudes and acceptance, with international tourists representing a key potential market. Therefore, it is recommended that the government, business actors, and the tourism industry enhance education efforts, expand product availability, and optimize promotion and information transparency to increase consumer interest in animal welfare products in Indonesia.